2011
DOI: 10.1103/physrevd.83.045007
|View full text |Cite
|
Sign up to set email alerts
|

Path integral quantization of generalized quantum electrodynamics

Abstract: In this paper, a complete covariant quantization of generalized electrodynamics is shown through the path integral approach. To this goal, we first studied the hamiltonian structure of system following Dirac's methodology and, then, we followed the Faddeev-Senjanovic procedure to obtain the transition amplitude. The complete propagators (Schwinger-Dyson-Fradkin equations) of the correct gauge fixation and the generalized Ward-Fradkin-Takahashi identities are also obtained. Afterwards, an explicit calculation o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 40 publications
5
65
0
Order By: Relevance
“…This is a major issue and certainly cannot be neglected, and requires a detailed study; nevertheless, once we have identified the primitive divergences on the 1P I functions [18] and the theory rendered UV finite (at the light of effective theories) we are motivated to retain some attention regarding the underlying aspects of the renormalized behavior of the present theory. We expect to obtain from comparison of our results to the regular expressions for the effective coupling and one-loop contribution for the anomalous magnetic moment, an energy regime of validity of the theory and a bound value for the free parameter, respectively.…”
Section: Renormalization Schedulementioning
confidence: 99%
See 4 more Smart Citations
“…This is a major issue and certainly cannot be neglected, and requires a detailed study; nevertheless, once we have identified the primitive divergences on the 1P I functions [18] and the theory rendered UV finite (at the light of effective theories) we are motivated to retain some attention regarding the underlying aspects of the renormalized behavior of the present theory. We expect to obtain from comparison of our results to the regular expressions for the effective coupling and one-loop contribution for the anomalous magnetic moment, an energy regime of validity of the theory and a bound value for the free parameter, respectively.…”
Section: Renormalization Schedulementioning
confidence: 99%
“…According to the Lagrangian (2) we obtain here new Schwinger-Dyson-Fradkin equations for the theory, which we shall denote by the suffix (R) . More precisely, the original self-energy functions [18] are changed by adding the counter-terms δ Zi . Now, by a formal derivation it is not complicated to show that the photon sector has the following renormalized self-energy function:…”
Section: Renormalization Schedulementioning
confidence: 99%
See 3 more Smart Citations